ANALISIS KELIMPAHAN POPULASI Telescopium telescopium DI KAWASAN KONSERVASI MANGROVE DAN BEKANTAN KOTA TARAKAN - Gazali, Salim; Rachmawani, Dori; Mathius, Kristiani Rani (Jurnal Harpodon Borneo, 2017)
Research objectives is to know abundance of offerings shared with percent of the population T.telescopium in a habitat of those mangrove KKMB the city of Tarakan. The research uses a method of descriptive method. The sample collection be paid out starting on different stations in the regions KKMB and stations 2 in the expansion of KKMB. Each station also carried out 6 plot with the size of 10x10 meters with the methods purposive the sampling method. The sample collection t.telescopium performed on recede lowest and extraction of secondary data of a variable pH, salinitas and at such a temperature (in-situ) and analysis of a sample of sediment. The results of the study abundance T.telescopium is highest in the expansion of the average value of station KKMB 0,102 ind/m2 and on the average value of station KKMB 0,088 ind/m2. Based on analysis substratum research the ground in two stations of different there are different substratum dominant the dust was 48% in KKMB and types of the substrate at the station KKMB down the dust was 51 %. Based on the results of the analysis that pH and the temperature at two stations of different having the value of the average the same situation namely that 7-8 and 27-28oC.The measurement result salinitas in both station average range 28ppt – 30ppt.